Corruption and pensosity: The suffering core of democracy - Cuomo, Elena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Corruption is a complex system. Corruptors operate on the material and cognitive levels to insert corruption into the shared ethos. The aim is to reflect on corruption in Western democracy, through an ethical, philosophical-political and anthropological understanding, with regard to subjectification, linked to identity and belonging that psychoanalysis and political symbolism investigate. The methodology will be multidisciplinary. The fertile ground for corruption is the lack of development of “thoughtfulness”, an interior and relational space in which, starting from the caregiver’s relationship with the infant, the conscious and responsible subject is built. For Mary Douglas it is necessary to study identity and belonging of a family or individualistic type.